MAINTAINING SERVICE QUALITY: EXAMINING THE EFFECT OF THE HESQUAL SCALE ON STUDENT SATISFACTION AT UNIVERSITIES (A STUDY OF STUDENTS AT NAHDLATUL ULAMA UNIVERSITY, YOGYAKARTA) - Budi Sutiono Pratama Nugraha Budi; Windriyati Windri (Jurnal Media Ekonomi (JURMEK), 2026)
Purpose: This study aims to examine the direct and indirect effects of HESQUAL-based service quality and technology support on student satisfaction by incorporating students’ perceived value as a mediating variable in a higher education context. Research Methodology: A quantitative explanatory research design was employed. Data were collected from 300 undergraduate students at Universitas Nahdlatul Ulama Yogyakarta using a structured questionnaire. The data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM) to test both direct and mediating relationships among variables. Results: The findings reveal that HESQUAL-based service quality has a significant positive effect on students’ perceived value and student satisfaction. Technology support also significantly influences both perceived value and satisfaction, although its effect is weaker compared to service quality. Furthermore, students’ perceived value significantly affects student satisfaction and functions as a mediating variable in the relationship between both service quality and technology support on satisfaction. Conclusions: Student satisfaction in higher education is determined not only by service quality and technological support but also by how students perceive the value of their educational experience. Perceived value plays a central role in translating institutional services into satisfaction outcomes. Limitations: This study is limited to a single university, which may restrict generalizability. The cross-sectional design also limits causal interpretation over time. Additionally, the model focuses only on four main constructs, excluding other potential influencing factors such as institutional image, trust, and student engagement. Contributions: This study contributes to higher education service quality literature by integrating HESQUAL, technology support, perceived value, and student satisfaction into a unified empirical model. It also extends prior research by empirically validating the mediating role of perceived value in a faith-based private university context